Komunikasi Interpersonal Anak dan Orangtua ditinjau dari Jenis Kelamin, Tingkat Pendidikan Orangtua, dan Daerah Tempat Tinggal serta Implikasinya pada Bimbingan dan Konseling - Aressa, Vivy; Nirwana, Herman; Bentri, Alwen (Universitas Negeri Padang, 2016)
Communication within the family is one of the means of parents instill the values to their children. This research background is the low skilled interpersonal communication of children and their parents. This study aimed to describe and examined: (1) interpersonal communication of children and parents in terms of sex, the last education of parent, and area of residence, (2) differences in interpersonal communication of children and parents in terms of sex, the last education of parent, and area of residence. The research methods applied in this research was ex post facto with factorial design 2 x 3 x 2. The population was students in SMAN 1 Maninjau and SMAN 1 Bukittinggi. The number of samples as much as 263 people were selected by cluster random sampling and combined with the technique propotional random sampling technique. The instruments used a Likert scale. Data were analyzed with descriptive statistics and using analysis of variance. Data analysis results showed that: (1) the general, interpersonal communication of children and parents in terms of sex, the last education of parents, and area of residence were in good category, (2) there are significant differences the variables sex, in the mean scores of female is higher than male students' the, the last education of parent and area of residence there are no differences significant. The implications of the results of this research can be used as input to create a program of guidance and counseling services, especially in the development of family.Â